Unlocking the power of set pieces in men’s professional football – a scoping review - Sarmento, Hugo; Afonso, José; Clemente, Filipe Manuel; Gouveia, Élvio Rúbio; Ordoñez-Saavedra, Nestor; Silva, João Renato; Barrera, Joel; Field, Adam; Martinho, Diogo V. (International Journal of Sports Medicine, 2025)
Set pieces represent a crucial moment in football analysis but have yet to receive as much attention as other football moments or physical and physiological elements. This systematic review summarized the literature surrounding set-pieces in professional football players. The studies were included if the sample comprised adult male football players competing in tiers 3–5, and set pieces were examined (i.e., penalties, corners, free kicks, and throw-ins). A total of 95 studies met the eligibility criteria. Most studies investigated penalties (44%) and corners (20%), while free-kicks and throw-ins have not yet been examined extensively. Characteristics of penalty kickers, penalty placement, goalkeepers’ actions and contextual factors affected the accuracy of penalties. Corners’ success was dependent on the type of delivery (i.e., inswing or outswing), the number of players in the penalty area and contextual factors. Constraints associated with the task, individual and environment were associated with the execution of free kicks. Throw-ins seemed essential to keep the ball in possession, although the literature was scarce. The characteristics of set pieces should take into account the defensive organization of the opposing team, as they are particularly important for creating goal-scoring opportunities and influencing the match result.
Keywords: performance; penalties; corners; free-kicks; throw-ins; ecological dynamic model